Step-by-step explanation:
I have no idea if I'm doing it right but my guess would be to take the values that we get from f(x) and g(x) when x = 1. Therefore we get that f(x) is equal to 4 and g(x) is equal to -1. We than just do f/g which is 4/-1 which gives us the final answer of -4 which is option B.
Answer: Option B, -4
-3(6x+5)-2(1-17x)=3(5+5x)
Mutiply the first bracket by -3
(-3)(6x)= -18x
(-3)(5)= -15
Mutiply the second bracket by -2
(-2)(1)= -2
(-2)(-17x)= 34x
Mutiply the third bracket by 3
(3)(5)= 15
(3)(5x)= 15x
-18x-15-2+34x= 15+15x
-18x+34x-15-2= 15+15x
16x-17= 15+15x
move 15 to the other side
sign changes from +15 to -15
16x-17-15= 15-15+15x
16x-32= 15x
move -32 to the other side
sign changes from -32 to +32
16x-32+32=15x+32
16x= 15x+32
move 15x to the other side
sign changes from +15x to -15x
16x-15x=15x-15x+32
x= 32
Answer: x= 32
Answer:
Twenty five
Step-by-step explanation:
Answer:
17
Step-by-step explanation:
1 because it's less than 2
Answer:
9
Step-by-step explanation:
30 - (9+4 x 3)
30 - (9 + 12)
30 - 21
= 9